ANALISIS PROTEIN PADA INSANG UDANG Macrobranchium sintangense (de Man) AKIBAT PERLAKUAN SALINITAS YANG BERBEDA - Anita Munawwaroh (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2017)
The study aimed to know the effect of different salinity on shrimp of protein content and protein profiles. The animal in this study was Macrobranchium sintangense shrimp with average length ± 50 mm which has acclimation for three days. The shrimp was treated at different salinity, the salinity 0 0/00, 5 0/00, 100/00,15 0/00 and 20 0/00 for seven days. Protein content and protein profiles by taking shrimp gill. Shrimp gill test showed that has a different protein content, protein profiles due to treatment of different salinity. The result was conclude that salinity 0 0/00, 5 0/00, 100/00,15 0/00 and 20 0/00 affect protein content and protein profiles of M. sintangense.